Epigenetic processes in sporadic parathyroid neoplasms. (5th July 2018) - Silva-Figueroa, Angelica M.; Perrier, Nancy D.
Abstract: Parathyroid tumors (PTs) are highly variable in their genetic background. Increasing evidence demonstrates that endocrine diseases can be caused by epigenetic alterations. The present review is focused on epigenetic aberrations related to PTs. DNA methylation, posttranslational histone modification, and noncoding RNAs are epigenetic mechanisms involved in parathyroid tumorigenesis. The information in this review has the potential to define epigenetic signatures associated with PTs for future use as diagnostic markers and lead to the development of new epigenetic drugs with therapeutic applications for these tumors. However, several epigenetic aspects regarding the biomarkers involved and their interactions in tumorigenesis on PTs are still unknown. Key to future epigenetic research would be a focus on global epigenetic identification of biomarkers in the different types of PTs, especially in parathyroid carcinoma. Better understanding may be useful for diagnostic and therapeutic uncertainty.